A Degradation study of polyurethane and polyfurfuryl alcohol resins under acidic environment - Bual, Ronald P. (2013)
The degradation reaction of polyurethane and polyfurfuryl alcohol resins in strong inorganic acids was investigated by obtaining their weight change with time and their FT-IR spectrum at various time intervals. Polyurethane and polyfurfuryl alcohol resins were immersed in 5M solution of HC1, H2SO4, and HNO3 at 30°C, 50°C, and 80°C using thermostat waterbaths. The spent acid solutions containing the degradation products were then neutralized and subjected to FT-IR analysis. Results show the strong dependence of diffusion coefficient to temperature and the type of acid used. Among the three temperatures, 80°C makes the reaction proceed the fastest. While among the three acids, HNO3 is the fastest to diffuse and degrade the polymer. The dissolution of polyfurfuryl alcohol resin in HNO3 was confirmed to proceed via breakage of -CH- and -CH2- groups near or between furan rings at around 3100 and 2900 cm ¹, respectively. Furthermore, the chemical decomposition of polyurethane proceeds via breakage of the aliphatic alkane in the urethane group producing amine and a polyol.
Thesis (M.S. Chemical Engineering)--University of the Philippines, Diliman
Keywords: Polyurethane